THE INFLUENCE OF ENVIRONMENTAL COSTS AND CARBON PERFORMANCE ON FINANCIAL PERFORMANCE: THE MEDIATING ROLE OF ENVIRONMENTAL PERFORMANCE - Amalia, Hanifah Adhe; Aji, Seto Satriyo Bayu (International Journal of Accounting Innovation, 2025)
Objective: This study investigates the intricate relationships between environmental costs, carbon performance, and financial performance within corporate frameworks. The primary objective is to elucidate how environmental performance mediates the relationship between carbon performance and financial outcomes. Method: The study employs a quantitative approach, utilizing purposive sampling to select a population of energy sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 17 companies were included in the final sample, resulting in 51 observations. Data collection techniques involved the use of financial reports and sustainability disclosures, while analysis was conducted using statistical software to perform regression analysis and hypothesis testing. Results: The results indicate that companies demonstrating robust carbon performance, characterized by reduced emissions, tend to experience enhanced environmental performance, which subsequently leads to improved financial performance. Novelty: The novelty of this research lies in its exploration of environmental costs as both a necessary expenditure and a strategic investment that can yield long-term financial benefits. It differentiates itself from prior studies by focusing specifically on the energy sector in Indonesia, providing new insights into how environmental initiatives can be leveraged for financial gain. Furthermore, it reinforces the notion that effective environmental management is not merely a regulatory obligation but a strategic investment that can yield significant returns.